COGNITIVE DOMAINS FOUND ON SPEAKING SKILL QUESTIONS USED IN ENGLISH LANGUAGE TEXTBOOK - Agustien Raquela; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This is a qualitative study of cognitive domains of speaking skill questions used in Interlanguage: English for Third Grade Senior High School. In this study, the writer observed the six categories of cognitive domains and the dominant order thinking skill applied in the questions on speaking skill. In order, to know the position of the student’s proficiency in the speaking skill questions used in this textbook. The data were collected from the textbook. The theory used was from Anderson and Krathwohl (2001) about Revised Bloom’s Taxonomy. This study showed that there were five from six categories of the cognitive domains applied in the questions on speaking skills used in the textbook, the dominant category was ‘remembering’ because in speaking skill students need to remember what they want to say and what people said. The writer found that the questions on speaking skill in this textbook belongs to lower order thinking skill because it was important for the students to master the lower order thinking skill before they achieve the higher order thinking.